Fertility indicators and its correlates among women in Iran - Jila Sadighi; Mahmoud Tavousi; Ali Montazeri; Ramin Mozafari Kermani; Mohammad Eslami; Rahele Rostami; Tahereh Rostami (Payesh, 2020)
Objective: The aim of this study was to investigate the fertility indicators in Iran. Methods: This was a cross-sectional study and included Iranian women of reproductive-age. The data were collected using a questionnaire and analyzed using SPSS18. Results: In all 10547 women included in the study. The mean live birth was 1.96 and it was increased as age of both women and husbands were increased; and it was decreased as age at marriage, age at birth of the first child, and education were increased. Live birth was more in low-income women and in rural areas. The frequency of stillbirth was 4.8% and increased as age of both women and husbands were increased. The stillbirth decreased as age at marriage, the age at birth of the first child, and education were increased. There was no relationship between stillbirth and women’s occupation, occupation of husbands, and religion. The stillbirth was more in low-income women and in rural areas. The frequency of abortion was 18.2% and increased with age of women, age of husbands, and age at birth of the first child. Abortion decreased with increased age at marriage and education. Abortion was more common in low-income women. Abortion had no relationship with women’s occupation, religion, and urban/rural residency. The frequency of the cesarean section was 42.1%. Cesarean increased with increased age of women and husbands, age at marriage, age at birth of the first child, and education. Delivery by cesarean had no relationship with occupation of husbands. The cesarean decreased with decreased income and was higher in urban areas. Conclusion: Investigating the trend of fertility indicators can play important role in identifying problems, planning for required services, and optimal allocation of resources. The findings from this study will complement the information that is needed by policy-makers.